Subject headings lists ahd thesaurus initiatives for equity and social justice. - Fabíola Rubim Silva; Paula Regina Dal'Evedove (Anales de Documentación)
The research aimed to describe initiatives for creating and updating subject heading lists and thesaurus considering social justice and equity, based on the literature from the sociocultural dimension of Knowledge Organization. As a methodological procedure, this applied research adopts a qualitative approach, using scoping review. The study identifies 27 initiatives for creating and updating subject heading lists and thesaurus focused on social justice and equity: Eight initiatives for gender, eight for indigenous groups, five for LGBTQIA+ community, five for race and ethnicity, and one for miscellaneous. The research identifies successful initiatives for constructing and updating subject heading lists and thesaurus to promote social justice and equity, especially those focused on indigenous communities. However, limited access to some of these systems is considered a barrier to expanding the initiatives’ dissemination.